2018
DOI: 10.1242/bio.031849
|View full text |Cite|
|
Sign up to set email alerts
|

Do wild-caught urban house sparrows show desensitized stress responses to a novel stressor?

Abstract: While urbanization exposes individuals to novel challenges, urban areas may also constitute stable environments in which seasonal fluctuations are buffered. Baseline and stress-induced plasma corticosterone (cort) levels are often found to be similar in urban and rural populations. Here we aimed to disentangle two possible mechanisms underlying such pattern: (i) urban environments are no more stressful or urban birds have a better ability to habituate to stressors; or (ii) urban birds developed desensitized st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
0
4
1
Order By: Relevance
“…Several local studies on plasma CORT support our finding, showing lower baseline (Wright and Fokidis, 2016) and stress-induced (Partecke et al, 2006;Wright and Fokidis, 2016) plasma CORT concentrations in urban birds. In contrast, other studies reported no overall differences in baseline plasma concentrations between urban and non-urban birds (H. Bobby Fokidis et al, 2009;Foltz et al, 2015;Grunst et al, 2014;Hudin et al, 2018;Injaian et al, 2020;Meillère et al, 2015), including captive blackbirds (Partecke et al, 2006). There are several potential explanations for these differences between our findings and those of previous studies.…”
Section: Discussioncontrasting
confidence: 91%
“…Several local studies on plasma CORT support our finding, showing lower baseline (Wright and Fokidis, 2016) and stress-induced (Partecke et al, 2006;Wright and Fokidis, 2016) plasma CORT concentrations in urban birds. In contrast, other studies reported no overall differences in baseline plasma concentrations between urban and non-urban birds (H. Bobby Fokidis et al, 2009;Foltz et al, 2015;Grunst et al, 2014;Hudin et al, 2018;Injaian et al, 2020;Meillère et al, 2015), including captive blackbirds (Partecke et al, 2006). There are several potential explanations for these differences between our findings and those of previous studies.…”
Section: Discussioncontrasting
confidence: 91%
“…Plasma 1α-hydroxycorticosterone was quantified using UPLC-MS/MS providing the needed accuracy and specificity as it was based on validated methods (Aerts et al, 2018; Salleh Hudin et al, 2018). The concentrations of 1α-hydroxycorticosterone in our study ranged between 0.01 and 0.83 μg/100 mL plasma (0.04–22.89 nM, including all control and air-exposed fish along the experimental period), and were found to be in the range previously described in the literature for this species (0.36 ± 0.1 μg/100 mL) as well as other species of shark such as spiny dogfish ( S. acanthias ) (2.3 ± 0.5 μg/100 mL), blue shark ( Prionace glauca ) (0.87 ± 0.05 μg/100 mL), shortfin mako ( Isurus oxyrinchus ) (5.3 μg/100 mL) and several other rays and skates species (0.08–4.7 μg/100 mL) measured by a wide range of techniques such as radioimmunoassay, thin layer chromatography coupled to fluorescence or double isotope derivative assay (Anderson, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The impact of anthropogenic disturbance is increasingly evident around the world (Seto et al, 2012), but our knowledge on how it impacts species phenotypes and genotypes is still rather limited (Johnson & Munshi-South, 2017). Previous research has shown that species usually show no or limited responses to anthropogenic disturbance (Bonier, 2012;Chavezzichinelli et al, 2010;Hudin et al, 2018;Sepp et al, 2018). In line with these results, the pace-of-life hypothesis predicts no differences in stress responses between urban and rural habitats (Sepp et al, 2018), but previous studies have been inconsistent in confirming this point with regard to BR variation, a proxy of acute stress responses to handling (Charmantier et al, 2017;Senar et al, 2017;Torné-Noguera et al, 2014).…”
Section: Br Of Tropical Passerines Support the Pace-oflife Hypothesismentioning
confidence: 99%
“…Inspired by previous research on rural-urban differences, the pace-of-life hypothesis suggests that individuals colonizing urban environments show a particular suite of life history traits (i.e., high investment in self-maintenance and low investment in reproduction), but also predicts no change in stress responses (Sepp, McGraw, Kaasik, & Giraudeau, 2018). Accordingly, most research on the topic has shown that species display limited or no changes in stress responses when exposed to anthropogenic disturbance (Bonier, 2012;Chavezzichinelli et al, 2010;Hudin et al, 2018;Sepp et al, 2018). This has raised the question whether urban areas are not particularly stressful habitats, or at least similarly stressful compared to natural environments, for the species able to colonize them.…”
Section: Introductionmentioning
confidence: 99%